2017
DOI: 10.1016/j.mib.2017.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Post-transcriptional regulation of type III secretion in plant and animal pathogens

Abstract: Type III secretion systems (T3SS) serve as a primary anti-host defense mechanism for many Gram-negative plant and animal pathogens. T3SS production is tightly controlled and activated by host-associated signals. Although transcriptional responses represent a significant component of the activation cascade, recent studies have uncovered diverse post-transcriptional mechanisms that also contribute to T3SS production. Targets for post-transcriptional control are often AraC/XylS transcription factors that promote … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 51 publications
1
14
0
2
Order By: Relevance
“…2,4,5). We found that, like injectisome systems, posttranscriptional mechanisms are also involved (82). Our model is also similar to feedback regulation of the flagellar T3SS system in Campylobacter jejuni.…”
Section: Discussionsupporting
confidence: 72%
“…2,4,5). We found that, like injectisome systems, posttranscriptional mechanisms are also involved (82). Our model is also similar to feedback regulation of the flagellar T3SS system in Campylobacter jejuni.…”
Section: Discussionsupporting
confidence: 72%
“…Regulation of the EspM transcription factor may be similar to the control of gene expression by type III secretion systems (T3SS) in Gram-negative bacteria (60)(61)(62)(63). The injectisome T3SS uses cytoplasmic substrates and/or chaperones to posttranscriptionally modulate the levels or activity of transcription factors that regulate secretion-associated genes (62,(64)(65)(66)(67)(68)(69). ESX-1 substrates or chaperones may posttranscriptionally regulate the activity of EspM in response to the presence or absence of the ESX-1 membrane complex.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial type III secretion system (T3SS) is known to play an important role during bacterial interaction with plants and animals [16,51]. However, knowledge about its involvement in bacterial-fungal interactions is limited.…”
Section: Discussionmentioning
confidence: 99%